2021
DOI: 10.3390/cancers13092162
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Artificial Intelligence Applications in Liver and Pancreatic Imaging

Abstract: Artificial intelligence (AI) is one of the most promising fields of research in medical imaging so far. By means of specific algorithms, it can be used to help radiologists in their routine workflow. There are several papers that describe AI approaches to solve different problems in liver and pancreatic imaging. These problems may be summarized in four different categories: segmentation, quantification, characterization and image quality improvement. Segmentation is usually the first step of successive elabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…For segmentation, there are some public datasets available for CT, like the LITS [56] and 3DIRCAD [101] but only CHAOS [102] for MRI. Increasing the amount of training data while providing multicentre acquisitions can boost the performance of AI models [103]. These multi-centre datasets must be heterogenous enough to eliminate biases relating to race, gender, ethnicity, and age.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…For segmentation, there are some public datasets available for CT, like the LITS [56] and 3DIRCAD [101] but only CHAOS [102] for MRI. Increasing the amount of training data while providing multicentre acquisitions can boost the performance of AI models [103]. These multi-centre datasets must be heterogenous enough to eliminate biases relating to race, gender, ethnicity, and age.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…The efficiency of AI algorithms to perform repetitive tasks, such as segmentation have already been shown to outperform manual approaches in various clinical studies. A study by Winkel D. et al [ 123 , 124 ] showed that their fully automated liver segmentation algorithm using deep learning was able to achieve a mean processing time of 9.94 s, at least 20 times faster than manual segmentation with excellent agreement between the two approaches (intraclass correlation coefficient of 0.996). In a polycystic liver and kidney disease series of CT images, an artificial intelligence model segmented the liver parenchyma at 8333 slices/hour, compared to labour intensive manual segmentation by an expert clinician, which did not surpass 16 slices/hour, with a DSC of 0.96 [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver is also a popular target for automated segmentation algorithms. Automatic segmentation of this organ is regarded as somewhat less challenging than that of the pancreas, with reported DSC scores typically in the > 0.90 range[ 35 ].…”
Section: Image Analysismentioning
confidence: 99%